Administrative reforms commission and right to information - Singh, Shekhar (2006)
The Administrative Reforms Commisison's recommendations on the RTI Act do not seem to be aimed at giving it more teeth. On the contrary, having failed to have in-depth consultation with groups working to promote RTI, it has actually arrived at avoidable conclusions. - Reproduced.
Keywords: Administrative Reforms Commission; Right to information